Acceptance tests of the industrial series manufacturing of WEST ITER-like tungsten actively cooled divertor. (24th September 2021) - Richou, Marianne; Missirlian, Marc; Firdaouss, Mehdi; Böswirth, Bernd; Diez, Mathilde; Greuner, Henri; Hatchressian, Jean-Claude; Pérot, Nadia; Ramaniraka, Manda; Roche, Hélène
Abstract: The activelly cooled plasma facing units (PFUs) constituting the WEST lower divertor must meet strict technical specifications before their installation into the WEST tokamak. The tests performed at CEA lead mainly: to provide information on the feasibility to attach mechanically PFUs on sectors, to ensure geometrical tolerances for the welding of PFUs to water manifolds, to check the PFU vacuum tightness and to confirm the PFUs heat exhaust capability. Using high heat flux (HHF) test facilities, such as HADES at CEA-Cadarache and GLADIS at IPP-Garching, ∼5% of the PFU production was tested. Infrared thermography (IR) tests were also performed (∼24% of the PFU production tested). We show that PFUs are with a quality in agreement to the requirements and that the assessement of the heat exhaust capability during the series production is needed. Based on statistical approaches, this work also provides information on the methods to assess the quality of tested components using statistic process control.